Electron emission characteristics of the porous polycrystalline silicon diode - Kim, H; Park, JW; Lee, JW; Lee, YH; Song, YH; Lee, JH; Cho, KI; Jang, J; Oh, MH; Ju, BK (ELSEVIER SCIENCE BV, 2002)
It is estimated that a porous polysilicon (PPS) diode with a structure of Au/PPS/n-type Si operates as an efficient stable surface emitting cold cathode. 2.0 mum of an non-doped polysilicon layer is formed on an heavily doped n-type silicon wafer and anodized in a solution of HF (50%):ethanol = 1:1 under illumination by a 500 W tungsten lamp from a distance of 20 cm. The electron emission properties of the PPS diode were investigated as a function of anodizing condition such as anodizing current density. The electron emission trajectory was investigated, and it was also demonstrated their good uniformity in the emitting area. (C) 2002 Published by Elsevier Science B.V.